INTEGRATIVE ECOTOXICOLOGICAL ASSESSMENT OF CONTAMINATED SEDIMENTS IN a COMPLEX TROPICAL ESTUARINE SYSTEM - Abessa, D. M. S.; Carr, R. S.; Sousa, E. C. P. M.; Rachid, B. R. F.; Zaroni, L. P.; Gasparro, M. R.; Pinto, Y. A.; Bicego, M. C.; Hortellani, M. A.; Sarkis, J. E. S.; Muniz, P.; Crane, JR; et al. (Nova Science Publishers, Inc, 2010)
The Santos Estuarine System (SES) is a complex of bays, islands, estuarine channels and rivers located on the Southeast coast of Brazil, in which multiple contaminant sources are situated in close proximity to mangroves and other protected areas. In the present study, the bottom sediment quality from the SES was assessed using the Sediment Quality Triad approach, which incorporates concurrent measures of sediment chemistry, toxicity and macrobenthic community structure. Elevated concentrations of metals were detected in the inner parts of the estuary, in the vicinity of outfalls, and in the eastern zone of Santos Bay. PAHs were found at high concentrations only in the Santos Channel. Anionic detergents were found throughout the system, with higher concentrations occurring close to the sewage outfall diffusers and in the Sao Vicente Channel. Sediments were considered toxic based on whole sediment tests with amphipods and porewater tests with sea urchin embryos. The observed toxicity appeared to coincide with proximity to contaminant sources. The macrobenthic community for the entire study area showed signs of stress, as indicated by low abundance, richness and diversity. The integrative approach suggested that both environmental factors and contaminants were responsible for the altered benthic community structure. The most critically disturbed area was the Santos Channel (upper portion), followed by the Sao Vicente and Bertioga Channels, and the immediate vicinity of the sewage diffusers.
Keywords: Sediment Quality Triad; Santos Estuarine System; pollution; toxicity; benthic communities; estuary; Brazil